Different approaches to long-term treatment of aHUS due to MCP mutations: a multicenter analysis - Klämbt, Verena; Gimpel, Charlotte; Bald, Martin; Gerken, Christopher; Billing, Heiko; Loos, Sebastian; Hansen, Matthias; König, Jens; Vinke, Tobias; Montoya, Carmen; Lange-Sperandio, Bärbel; Kirschstein, Martin; et al. (Pediatric nephrology, 2021)
Atypical hemolytic uremic syndrome (aHUS) is a rare, life-threatening microangiopathy, frequently causing kidney failure. Inhibition of the terminal complement complex with eculizumab is the only licensed treatment but mostly requires long-term administration and risks severe side effects. The underlying genetic cause of aHUS is thought to influence the severity of initial and recurring episodes, with milder courses in patients with mutations in membrane cofactor protein (MCP).